Economic and Financial Crime Corruption, shadow economy, and money laundering - Achim, Monica Violeta; Borlea, Sorin Nicolae; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book deals with the widespread economic and financial crime issues of corruption, the shadow economy and money laundering. It investigates both the theoretical and practical aspects of these crimes, identifying their effects on economic, social and political life. This book presents these causes and effects with a state of the art review and with recent empirical research. It compares the international and transnational aspects of these economic and financial crimes through discussion and critical analysis. This volume will be of interest to researchers and policy makers working to study and prevent economic and financial crime, white collar crime, and organized crime.
Chapter 1 . Economic and financial crime:theoretical and methodological approaches -- Chapter 2. Economic and political determinants of economic and financial crime -- Chapter 3. Behavioural determinants of economic and financial crime -- Chapter 4. Effects of economic and financial crimes: ways of fighting against.
Keywords: White collar crimes; Organized crime; Economic sociology; White Collar Crime; Organized Crime; Organizational Studies, Economic Sociology